Fertilized graminoids intensify negative drought effects on grassland productivity. (21st March 2021) - Van Sundert, Kevin; Arfin Khan, Mohammed A. S.; Bharath, Siddharth; Buckley, Yvonne M.; Caldeira, Maria C.; Donohue, Ian; Dubbert, Maren; Ebeling, Anne; Eisenhauer, Nico; Eskelinen, Anu; Finn, Alain; Gebauer, Tobias; et al.
Abstract: Droughts can strongly affect grassland productivity and biodiversity, but responses differ widely. Nutrient availability may be a critical factor explaining this variation, but is often ignored in analyses of drought responses. Here, we used a standardized nutrient addition experiment covering 10 European grasslands to test if full‐factorial nitrogen, phosphorus, and potassium addition affected plant community responses to inter‐annual variation in drought stress and to the extreme summer drought of 2018 in Europe. We found that nutrient addition amplified detrimental drought effects on community aboveground biomass production. Drought effects also differed between functional groups, with a negative effect on graminoid but not forb biomass production. Our results imply that eutrophication in grasslands, which promotes dominance of drought‐sensitive graminoids over forbs, amplifies detrimental drought effects. In terms of climate change adaptation, agricultural management would benefit from taking into account differential drought impacts on fertilized versus unfertilized grasslands, which differ in ecosystem services they provide to society. Abstract : Drought impacts on grasslands vary widely. Nutrient availability may be a critical factor explaining this variation. We used a standardized nutrient addition experiment covering 10 European grasslands to test if nitrogen, phosphorus, and potassium addition affected responses to inter‐annual variation in drought stress and to the extreme summer drought of 2018. We found that nutrient addition amplified detrimental drought effects on biomass production. Drought effects differed between functional groups, with a negative effect on graminoids but not forbs. For climate change adaptation, agricultural management would benefit from taking into account differential drought impacts on fertilized versus unfertilized grasslands, which differ in ecosystem service provisioning.